The Mitre: Its Origins and Early Development - Spies, Nancy, (Art and Material Culture in Medieval and Renaissance Europe ;, 2024)
The story of the mitre began during the 11th-century church reform movements and was, surprisingly, inspired by a popular pastime. After a thousand years of bare heads, the Church finally had an official hat, signaling newly-structured internal dynamics, an increase in power and influence in society, and greater parity with secular leaders.